LÂMINA ÓTIMA DE DEPLEÇÃO PARA A IRRIGAÇÃO DA CULTURA DA BATATA CULTIVARES ÁGATA E ATLANTIC - Silva, Edinéia Ferreira da (2015)
The potato (Solanum tuberosum L.) is a crop that has high demand in management and cultivation practices for that occur the increase of its production and yield. Among these hydric management is demonstrated as a major factor for the crop. In this way, the objective of the search it was to verify the influence of different levels of water depletion in the soil on agronomic characteristics of potato cultivation for cultivars Ágata and Atlantic, determining its influence on the morphology of the plant, production components, productivity and classification of tubers as its size, as well as the incidence and severity of diseases and pests besides the occurrence of physiological effects. The research was realized in Guarapuava-PR at the Department of Agronomy in the area of potato crop and Microclimate at the Universidade Estadual do Centro Oeste (latitude: 25°23`02"S, longitude: 51°29`43"W). The experiment consisted of two studus, one for each cultivar, using a completely randomized design (DIC), with 4 blades water depletion (12, 24, 36 and 48 mm) totaling 16 experimental units with 4.0 m? and 20 plants per unit. For statistical analysis we used the SAS® program version 9.2, the data were subjected to analysis of variance and regression with a significance level of 95% and after, were subjected to check of waste normality by the Shapiro-Wilk test and the homogeneity of variances by Bartlett test with probability confidence of 95%. In the evaluation at the shoat dry matter the best blade for cv. Ágata was 20.66 mm and 12 mm for cv. Atlantic, the highest leaf area index (LAI) was obtained with blade of 18.69 mm for cv. Ágata and 12 mm for cv. Atlantic. In the classification of tubers size the commercial class II (45-85 mm) presented the highest number of tubers for both cultivars. The highest yield of cv. Ágata was found with blade 27.62 mm with 32,981 kg ha?¹ and cv. Atlantic with 28.70 mm 25,580 kg ha?¹. For the cv. Agate the 48 mm blade depletion obtained the highest number of tubers with lower mass (70.20 g tuber-1) and the greatest mass was obtained with the blade of 27.41 mm. Significant effects were observed only for incidence and severity of silver scabies (Helminthosporium solani), with larger effect in the blade of 46.80 mm for the cv. Ágata and 36.86 mm for the cv. Atlantic.